The Verbal Expression of Anger in Croatian Comedy Films - Vlašić Duić, Jelena (Poznańskie Studia Slawistyczne, 2015)
The purpose of this paper was to examine the verbal expression of anger in Croatian comedy films and also to find textual and prosodic elements that provoke the viewer’s exhilaration. On the textual level analysis includes elements with which anger causes exhilaration and shows that such anger most often expresses superiority and is also unexpected which often occurs as a result of exaggeration. Due to the specific genre of comedy, i.e. its guaranteed lack of seriousness, the viewers are not aware of high presence of anger in film comedies. Comedy requires a different insight to life situations and a reinterpretation that leads to pleasant emotions.